2018
DOI: 10.1186/s12936-018-2633-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale field evaluation of the efficacy and residual effect of Fludora® Fusion (mixture of clothianidin and deltamethrin) against susceptible and resistant Anopheles gambiae populations from Benin, West Africa

Abstract: BackgroundIn recognition of the threat of insecticide resistance in vectors of malaria, the WHO Global Malaria Programme recommends the development of an appropriate and comprehensive response to insecticide resistance. In principle, good resistance management practice requires the application of multiple insecticides of different modes of action, for example, in rotations and mixtures. Insecticides recommended by the World Health Organization for indoor residual spraying and long-lasting insecticide nets are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 16 publications
2
50
1
Order By: Relevance
“…compared to deltamethrin on both mud and concrete substrates. The results confirm previous findings across Africa [ 11 , 15 , 16 ], thus demonstrating the suitability of Fludora® Fusion for indoor residual spraying in Benin and other malaria-endemic areas which are characterised by high intensities of pyrethroid resistance in local mosquito vectors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…compared to deltamethrin on both mud and concrete substrates. The results confirm previous findings across Africa [ 11 , 15 , 16 ], thus demonstrating the suitability of Fludora® Fusion for indoor residual spraying in Benin and other malaria-endemic areas which are characterised by high intensities of pyrethroid resistance in local mosquito vectors.…”
Section: Discussionsupporting
confidence: 89%
“…The low mortality response with deltamethrin IRS in the experimental huts is very typical of studies conducted in this area of Benin [ 11 , 14 ] thus demonstrating the redundancy of solo pyrethroid products for IRS and further highlighting the need for novel non-pyrethroid IRS insecticides. Studies performed with Fludora® Fusion in West Africa have so far reported its efficacy on treated surfaces only in cone bioassays [ 15 , 16 ] which generally do not take into consideration the behaviour of vector mosquitoes. Our study demonstrates for the first time the efficacy of Fludora® Fusion against wild free-flying pyrethroid-resistant malaria vectors in household settings in Benin.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are new insecticide classes and insecticide mixtures that have shown potential for replacing DDT, which is the current gold standard. [18,19] The main drawback of the new insecticides is the cost of purchasing them as well as their application. Drug resistance is also on the increase, beginning in the early 1980s with resistance to chloroquine, followed by resistance to sulfadoxine-pyrimethamine in the mid-to late 1990s.…”
Section: Insecticide and Drug Resistancementioning
confidence: 99%
“…The question of who should pay to obtain this evidence also remains open. While higher levels of mortality of pyrethroid-resistant vector populations have been reported with other recently developed novel IRS insecticides in similar trials [7,[13][14][15], effective rotation of IRS insecticides for insecticide resistance management as recommended by the GPIRM will require a much larger and more diversified portfolio of IRS insecticides [2].…”
Section: Discussionmentioning
confidence: 99%
“…As a strategy for managing insecticide resistance in local vector populations, vector control programmes are encouraged to implement a rotational schedule of IRS insecticides of different modes of action to reduce selection pressure on the vector [11]. While the newly prequalified IRS insecticides show potential to improve the control of insecticide-resistant vector populations [12][13][14][15], an effective rotational strategy which will prevent the development of further resistance cannot rely on these compounds alone as they contain the same active ingredient (clothianidin) and thus share the same mode of action; a more diversified portfolio of IRS insecticides is required.…”
Section: Introductionmentioning
confidence: 99%